Gross National Product And Gross Domestic Product In Measurement Of Community Welfare - Muhammad Afdhal Arrazak (Institut Agama Islam Sumatera Barat, 2024)
This article aims to discuss GNP and GDP as the main indicators in measuring community welfare. The research method used in writing this article is library research or literature study. The research results show that GNP reflects the total value of services and goods obtained by citizens, both inside and outside the country, while GDP only calculates the value of production within a country's geographical boundaries. Furthermore, in considering production factors, GNP measures the total production produced by a country's citizens, both within the country and abroad. Meanwhile, GDP only includes production that occurs within the country itself. In terms of the influence of income from abroad, GNP also takes into account the income earned by citizens from abroad and reduces the income received by foreign citizens residing in the country. In contrast, GDP does not consider the income received by citizens from abroad.